2013
DOI: 10.1021/jm4006324
|View full text |Cite
|
Sign up to set email alerts
|

Ligand–Protein Interactions of Selective Casein Kinase 1δ Inhibitors

Abstract: Casein kinase 1δ (CK1δ) and 1ε (CK1ε) are believed to be necessary enzymes for the regulation of circadian rhythms in all mammals. On the basis of our previously published work demonstrating a CK1ε-preferring compound to be an ineffective circadian clock modulator, we have synthesized a series of pyrazole-substitued pyridine inhibitors, selective for the CK1δ isoform. Additionally, using structure-based drug design, we have been able to exploit differences in the hinge region between CK1δ and p38 to find selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
(78 reference statements)
2
25
0
Order By: Relevance
“…Furthermore, core catalytic residues Lys38 and Asp149 [ 13 , 31 ] coordinate a structural water within the catalytic cleft which donates another hydrogen bond towards an imidazole nitrogen of the respective inhibitor. Gatekeeper residue Met82 is rotated by 180° towards Pro66 [ 13 , 31 ], thereby permitting access to the hydrophobic pocket I ( selectivity pocket , HPI ) [ 2 , 34 ] which is ideally occupied by the 4-fluorophenyl moiety [ 31 , 35 ]. Molecular modeling further suggests five-membered heterocycles to dictate an ideal angle for positioning of the vicinal aryl moieties within the ATP-binding pocket of CK1δ [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, core catalytic residues Lys38 and Asp149 [ 13 , 31 ] coordinate a structural water within the catalytic cleft which donates another hydrogen bond towards an imidazole nitrogen of the respective inhibitor. Gatekeeper residue Met82 is rotated by 180° towards Pro66 [ 13 , 31 ], thereby permitting access to the hydrophobic pocket I ( selectivity pocket , HPI ) [ 2 , 34 ] which is ideally occupied by the 4-fluorophenyl moiety [ 31 , 35 ]. Molecular modeling further suggests five-membered heterocycles to dictate an ideal angle for positioning of the vicinal aryl moieties within the ATP-binding pocket of CK1δ [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…CK1δ was modelled from the 3D crystallographic structure corresponding to the entry 4KBK that contains the crystallographic ligand 1QG. Only chain B, since it is naturally a monomer, was considered for further studies [ 64 ]. DYRK1A was modelled from the crystal 3D structure with a PDB ID 4AZE that contains the crystallographic ligand 3RA.…”
Section: Methodsmentioning
confidence: 99%
“…It was carried out through a bibliographical search plus a database analysis. The bibliographical search was conducted using several studies in which inhibitors against the selected kinases were identified describing each compound binding mode [ 25 , 31 , 32 , 50 , 51 , 52 , 64 , 81 , 82 ]. The database search was done using an in-house, recently constructed database.…”
Section: Methodsmentioning
confidence: 99%
“…AD is not an exception, and several drug candidates have been developed from natural sources against the different therapeutic targets identified to date [ 21 , 22 , 23 ]. In fact, few reasonable selective and potent GSK3β, CK1δ, DYRK1A, and CLK1 inhibitors have been described so far, most of them being marine natural products or derived molecules from them [ 5 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%